Urban epiphytes: Bromeliad diversity in a green cover gradient across a Neotropical streetscape - Aoki-Gonçalves, Felipe; Pena, João Carlos [UNESP]; Toledo-Aceves, Tarin; MacGregor-Fors, Ian (Elsevier, 2023)
The Neotropical region is undergoing high levels of urban expansion and harbors the greatest diversity of vascular epiphytes globally. In cities, it could be expected that the density of woody vegetation positively predicts epiphyte communities by providing substrate, resources for pollinators, and buffering microclimatic conditions. However, there is a dearth of knowledge regarding how urbanization intensity affects the diversity of vascular epiphytes. In this study, we assessed the relationship between a woody cover gradient and bromeliad species richness and community composition across a streetscape of the Neotropical city of Xalapa (Mexico). We recorded bromeliads in nine street segments and one peri-urban green space. These sites represent a gradient of woody cover ranging from 10.5% to ∼87% in a 100 m buffer, and 100% in the peri-urban green space. We recorded 824 individuals of 14 species (all from the Tillandsioideae subfamily). The most abundant species was Tillandsia recurvata and the most frequent ones were T. juncea and T. schiedeana. Results show that bromeliad species richness was positively related to the woody cover, as expected. Interestingly, community composition did not associate with the percentage of woody cover. These results suggest that additional factors such as microclimatic conditions and seed availability and/or dispersal may be key modulators on the establishment of bromeliad species. Nevertheless, wooded streets do show potential for harboring diverse bromeliad communities.
Keywords: City; Streetscape; Tillandsioideae; Urban Ecology; Urban vegetation; Woody cover